Acid-resistant COFs material capable of rapidly and efficiently adsorbing thorium ions and preparation method of acid-resistant COFs material
COFs materials prepared by reaction of aldehydes and amine monomers solve the problems of low stability and adsorption efficiency of existing adsorbents in a strong acid environment, and achieve efficient adsorption of thorium ions and maintain long-term adsorption performance.
Patent Information
- Application Number
- CN202411060689.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-05
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2044-08-05
AI Technical Summary
Existing adsorbents are difficult to maintain stability and efficient adsorption of thorium ions in strong acid environments, especially under conditions of pH < 3, and have low selectivity and rate.
Use aldehyde monomer trialdehyde phthalol and amine monomer 2,5-diaminoterephthalic acid or 4,4'-diamino-[1,1'-biphenyl]-3,3'- The covalent organic frame (COFs) material prepared by dicarboxylic acid reaction is formed by ultrasonic mixing, liquid nitrogen freezing, flame sealing and heating crystallization.
Under strong acid conditions (pH=1-3), the maximum adsorption capacity reaches 696 mg/g within 10 hours, and the adsorption capacity basically remains undecreased after 5 cycles, showing excellent regeneration cycle performance .
Smart Images

Figure CN119119402A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of material preparation, and in particular to an acid-resistant COFs material capable of rapidly and efficiently adsorbing thorium ions and a preparation method thereof. Background Art
[0002] With rapid industrial expansion and rising energy demand, nuclear energy, as a sustainable, stable, low-carbon energy source, plays an irreplaceable role in the global energy system. The recovery and purification of actinides is the central link in the nuclear fuel cycle and one of the most complex and challenging chemical processing processes known to date. Due to the radioactivity and high toxicity of thorium and its indispensable role in the sustainable development of nuclear energy, its recovery and purification are crucial.
[0003] Thorium in aqueous solution is tetravalent (Th(IV)), and its migration and diffusion process are greatly affected by pH value. 4+ It begins to hydrolyze strongly and can be completely precipitated at pH = 5-6. At pH < 4, Th (IV) is easier to diffuse and migrate, and has better solubility, so it is very difficult to remove. At present, the main methods for removing thorium ions include solvent extraction, membrane separation, chemical precipitation and adsorption. Among them, the adsorption method is considered to be an effective means of separating actinides, with the advantages of low energy consumption, convenient operation and less secondary waste. Adsorbents for Th (IV) ions that have been reported include carbon-based materials, zeolites, natural minerals, biomass, etc. Although these adsorbents are low in cost, they have disadvantages such as low adsorption capacity, slow adsorption rate and poor selectivity. In addition, when used under high acidity conditions in the nuclear industry, most absorbents find it difficult to maintain good stability and functionality at the same time. Therefore, there is an urgent need to develop new functional materials for effective adsorption and separation of thorium in a strongly acidic environment.
[0004] Metal organic frameworks (MOFs) and covalent organic frameworks (COFs) can show high structural designability through customized linker and node functions. MOF materials have been widely studied in the adsorption of Th(IV) ions, but the structural stability of MOF materials is poor in harsh environments. In contrast, COFs materials show high chemical stability in harsh environments due to their covalent bond connection, but the existing COFs materials are difficult to achieve efficient and highly selective adsorption of thorium in strong acid environments (pH <3), and even do not adsorb at all in the pH range of 1-2. Summary of the invention
[0005] In view of this, the present invention proposes an acid-resistant COFs material that can quickly and efficiently adsorb thorium ions and a preparation method thereof to solve the above problems. The COFs material prepared by the present invention has important scientific research significance and practical application value for the adsorption of thorium ions in nuclear wastewater.
[0006] The technical solution of the present invention is achieved in this way:
[0007] An acid-resistant COFs material for fast and efficient adsorption of thorium ions, prepared by the reaction of aldehyde monomer trialdehyde phloroglucinol and amine monomer;
[0008] The amine monomer is 2,5-diaminoterephthalic acid or 4,4'-diamino-[1,1'-biphenyl]-3,3'-dicarboxylic acid.
[0009] Furthermore, the molar ratio of the aldehyde monomer to the amine monomer is 1:1-2.5.
[0010] A method for preparing an acid-resistant COFs material for fast and efficient adsorption of thorium ions, the specific steps comprising: adding aldehyde monomers and amine monomers into an organic solvent, ultrasonically mixing them uniformly, then adding a catalyst, freezing with liquid nitrogen, evacuating, flame sealing, heating for crystallization, Soxhlet extraction, washing and drying to obtain the target COFs material.
[0011] Furthermore, the organic solvent is 1,4-dioxane and mesitylene in a volume ratio of 1:1-9 or n-butanol and o-dichlorobenzene in a volume ratio of 1:1-4.5.
[0012] Furthermore, the solid-to-liquid ratio of the aldehyde monomer and the amine monomer to the organic solvent is 4.8-33.33 mg / mL.
[0013] Furthermore, the catalyst is an aqueous solution of acetic acid with a concentration of 6-12 mol / L; the volume ratio of the catalyst to the organic solvent is 1:5-9.3.
[0014] Furthermore, the ultrasonication time is 8-12 minutes.
[0015] Furthermore, the temperature of the heating crystallization is 100-160° C., and the time is 3-9 days.
[0016] Application of the COFs material obtained by any of the preparation methods in the rapid and efficient adsorption of thorium ions.
[0017] Furthermore, the pH of the thorium ion solution is 1-3.
[0018] Compared with the prior art, the present invention has the following beneficial effects:
[0019] The functionalized COFs material prepared by regulating the grafted carboxyl group has excellent thorium ion adsorption performance and high adsorption capacity under strong acid conditions (pH=1-3), wherein the maximum adsorption amount is 696 mg / g within 10 hours under the conditions of initial concentration C0=400 ppm and pH=3, and the maximum adsorption amount is 225 mg / g within 10 hours under the conditions of initial concentration C0=400 ppm and pH=1. At the same time, it has high stability in a strong acid environment and shows excellent regeneration cycle performance. Its adsorption capacity does not decrease after 5 cycles of cyclic adsorption experiments. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 It is the adsorption principle diagram of the present invention;
[0021] Figure 2 is the XPS spectrum of TP-DAT-COF of Example 1;
[0022] Figure 3 It is the adsorption effect diagram of Example 1 (TP-DAT-COF) and Example 2 (TP-DBA-COF) at different cycle times;
[0023] Figure 4 It is the adsorption effect diagram of comparative examples 1-3 under different cycle numbers. DETAILED DESCRIPTION
[0024] In order to better understand the technical content of the present invention, specific embodiments are provided below to further illustrate the present invention.
[0025] Unless otherwise specified, the experimental methods used in the embodiments of the present invention are all conventional methods.
[0026] Unless otherwise specified, the materials, reagents, etc. used in the embodiments of the present invention can be obtained from commercial sources.
[0027] The trialdehyde phloroglucinol, 2,5-diaminoterephthalic acid, 4,4'-diamino-[1,1'-biphenyl]-3,3'-dicarboxylic acid, benzidine, 3,3'-dimethoxybenzidine and 3,3'-dihydroxybenzidine of the present invention were all purchased from Huaifang Xiaoyuan Chemical Economic and Trade Co., Ltd.
[0028] Abbreviation
[0029]
[0030]
[0031] Example 1
[0032] TP (7 mg, 0.033 mmol) and DAT (8 mg, 0.054 mmol) were added to a 10 mL Pyrex tube, and then added to a mixed organic solvent (0.9 mL of mesitylene and 0.1 mL of 1,4-dioxane), ultrasonically mixed for 10 min, acetic acid aqueous solution (6 mol / L, 0.2 mL) was added, liquid nitrogen was frozen, vacuumed, flame-sealed, heated at 120 ° C for 3 days, extracted with tetrahydrofuran Soxhlet for 24 h, washed, and vacuum dried at 120 ° C for 12 h to obtain a red powder covalent organic framework material COFs material, named TP-DAT-COF.
[0033] The structural formula of TP-DAT-COF is:
[0034]
[0035] Example 2
[0036] TP (9.5 mg, 0.045 mmol) and DBA (19 mg, 0.069 mmol) were added to a 10 mL Pyrex tube, and then added to a mixed organic solvent (0.55 mL of mesitylene and 0.45 mL of 1,4-dioxane), ultrasonically mixed for 10 min, acetic acid aqueous solution (6 mol / L, 0.2 mL) was added, liquid nitrogen frozen, evacuated, flame sealed, heated at 120 ° C for 3 days, extracted with acetone Soxhlet for 24 h, washed, and vacuum dried at 120 ° C for 12 h to obtain a red powder covalent organic framework material COFs material, named TP-DBA-COF.
[0037] The structural formula of TP-DBA-COF is:
[0038]
[0039] Example 3
[0040] TP (10 mg, 0.047 mmol) and DAT (10 mg, 0.067 mmol) were added to a 10 mL Pyrex tube, and then added to a mixed organic solvent (0.5 mL of n-butanol and 0.6 mL of o-dichlorobenzene), ultrasonically mixed for 10 min, acetic acid aqueous solution (12 mol / L, 0.2 mL) was added, liquid nitrogen frozen, evacuated, flame sealed, heated at 120 ° C for 3 days, extracted with N, N-dimethylformamide Soxhlet for 24 h, washed, and vacuum dried at 120 ° C for 12 h to obtain a red powder covalent organic framework material COFs material, named TP-DAT-COF.
[0041] Example 4
[0042] TP (7 mg, 0.033 mmol) and DBA (15 mg, 0.054 mmol) were added to a 10 mL Pyrex tube, and then added to a mixed organic solvent (0.5 mL of n-butanol and 1.0 mL of o-dichlorobenzene), ultrasonically mixed for 10 min, acetic acid aqueous solution (12 mol / L, 0.2 mL) was added, liquid nitrogen frozen, evacuated, flame sealed, heated at 120 ° C for 3 days, extracted with ethanol Soxhlet for 24 h, washed, and vacuum dried at 120 ° C for 12 h to obtain a red powder covalent organic framework material COFs material, named TP-DBA-COF.
[0043] Comparative Example 1
[0044] The difference from Example 1 is that the DAT of the amine monomer is replaced by BD, and the rest is the same as Example 1.
[0045] TP (7 mg, 0.033 mmol) and BD (8 mg, 0.043 mmol) were added to a 10 mL Pyrex tube, and then added to a mixed organic solvent (0.9 mL of mesitylene and 0.1 mL of 1,4-dioxane), ultrasonically mixed for 10 min, acetic acid aqueous solution (6 mol / L, 0.2 mL) was added, liquid nitrogen frozen, evacuated, flame sealed, heated at 120 ° C for 3 days, extracted with tetrahydrofuran Soxhlet for 24 h, washed, and vacuum dried at 120 ° C for 12 h to obtain a yellow powder covalent organic framework material COFs material, named TP-BD-COF.
[0046] The structural formula of TP-BD-COF is:
[0047]
[0048] Comparative Example 2
[0049] The difference from Example 1 is that the DAT of the amine monomer is replaced by DMB, and the rest is the same as Example 1.
[0050] TP (6 mg, 0.028 mmol) and DMB (8 mg, 0.032 mmol) were added to a 10 mL Pyrex tube, and then added to a mixed organic solvent (0.9 mL mesitylene and 0.1 mL 1,4-dioxane), ultrasonically mixed for 10 min, acetic acid aqueous solution (6 mol / L, 0.2 mL) was added, liquid nitrogen was frozen, vacuumed, flame sealed, heated at 120 ° C for 3 days, extracted with tetrahydrofuran Soxhlet for 24 h, washed, and vacuum dried at 120 ° C for 12 h to obtain a red powder covalent organic framework material COFs material, named TP-DMB-COF. The structural formula of TP-DMB-COF is:
[0051]
[0052] Comparative Example 3
[0053] The difference from Example 1 is that the DAT of the amine monomer is replaced by DHB, and the rest is the same as Example 1.
[0054] TP (7 mg, 0.033 mmol) and DHB (8 mg, 0.032 mmol) were added to a 10 mL Pyrex tube, and then added to a mixed organic solvent (0.9 mL of mesitylene and 0.1 mL of 1,4-dioxane), ultrasonically mixed for 10 min, acetic acid aqueous solution (6 mol / L, 0.2 mL) was added, liquid nitrogen frozen, evacuated, flame sealed, heated at 120 ° C for 3 days, extracted with tetrahydrofuran Soxhlet for 24 h, washed, and vacuum dried at 120 ° C for 12 h to obtain a red powder covalent organic framework COFs material, named TP-DHB-COF.
[0055] The structural formula of TP-DHB-COF is:
[0056]
[0057] Test Example 1
[0058] 2 mg of the covalent organic framework materials COFs prepared in Examples 1-4 and Comparative Examples 1-3 were respectively weighed and added into 6 mL of thorium solution for adsorption experiment (initial concentration C0 = 100 ppm, pH = 1-3) at a rotation speed of 330 rpm. After 10 hours, the adsorption capacity was calculated.
[0059] Q=[(C0-C t )×V] / m
[0060] Where Q is the adsorption capacity, in mg / g; C0 is the initial concentration of thorium ions, in ppm; C t is the concentration of thorium ions after 10 hours, in ppm; V is the volume of the thorium solution, in L; m is the mass of the prepared COFs material adsorbent, in g.
[0061] The results are shown in Table 1.
[0062] Table 1
[0063]
[0064]
[0065] As can be seen from Table 1, under the conditions of an initial concentration of 100 ppm and a pH of 1-3, the COFs materials grafted with carboxyl groups of the present invention (Examples 1-4) all have an adsorption effect on Th(IV), and are significantly better than the COFs materials of Comparative Examples 1-3, indicating that the COFs materials prepared in Examples 1-4 of the present invention can achieve effective adsorption of thorium under strong acid conditions.
[0066] Test Example 2
[0067] 2 mg of the covalent organic framework materials COFs prepared in Examples 1-4 and Comparative Examples 1-3 were respectively weighed and added into 6 mL of thorium solution for adsorption experiment (initial concentration C0 = 100 ppm, pH = 4-5) at a rotation speed of 330 rpm. After 10 hours, the adsorption capacity was calculated.
[0068] The results are shown in Table 2.
[0069] Table 2
[0070]
[0071]
[0072] As can be seen from Table 2, when the initial concentration is 100 ppm and the pH is 4-5, the adsorption capacity of the COFs materials prepared in Examples 1-4 and Comparative Examples 1-3 reaches saturation (theoretical adsorption capacity), and there is no difference in the adsorption effect. Therefore, the COFs materials prepared by the present invention can achieve effective adsorption of thorium in the range of pH = 1-5, and preferably adsorb Th (IV) under strong acid conditions (pH = 1-3).
[0073] Test Example 3
[0074] 2 mg of the covalent organic framework materials COFs prepared in Examples 1-4 and Comparative Examples 1-3 were respectively weighed and added into 6 mL of thorium solution for adsorption experiment (initial concentration C0 = 400 ppm, pH = 1-3) at a rotation speed of 330 rpm. After 10 hours, the adsorption capacity was calculated.
[0075] The results are shown in Table 3.
[0076] Table 3
[0077]
[0078] As can be seen from Table 3, when the initial concentration is 400ppm and the pH is 1-3, the adsorption capacity of Th(IV) by the carboxyl functionalized COFs materials prepared in Examples 1-4 is better than that by the COFs materials prepared in Comparative Examples 1-3. The carboxyl functionalized COFs material prepared in Example 1 has a maximum adsorption capacity of 225mg / g within 10h at pH=1, and a maximum adsorption capacity of 696mg / g within 10h at pH=3, indicating that the functionalized COFs material grafted with carboxyl groups in Example 1 of the present invention can achieve a high adsorption capacity for thorium under strong acid conditions.
[0079] from Figure 2 The XPS spectrum of TP-DAT-COF shows that after adsorption of Th(IV), TP-DAT-COF shows obvious Th 4f 5 / 2 and Th 4f 7 / 2 The signal peak indicates that Th(IV) is successfully adsorbed. In addition, the electron binding energy corresponding to the O1s orbital signal peak on the carboxyl group in the sample after adsorption shifts, indicating that the carboxyl group in the functionalized COFs material of Example 1 has a coordination interaction with Th(IV).
[0080] from Figure 3-4 It can be seen from the adsorption effect diagram of different COFs materials under different cycle numbers that after 5 cyclic adsorption experiments (initial concentration of 100ppm, pH=3), the adsorption amount of the carboxyl functionalized COFs materials prepared in Example 1 (TP-DAT-COF) and Example 2 (TP-DBA-COF) remains almost unchanged, indicating that the carboxyl functionalized COFs materials prepared by the present invention have high stability under strong acid conditions and good regeneration cycle performance. After 5 cyclic adsorption experiments, the adsorption capacity of the COFs materials prepared in Comparative Examples 1-3 decreased significantly, indicating poor stability under strong acid conditions and poor regeneration cycle performance.
[0081] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. An acid-resistant COFs material for fast and efficient adsorption of thorium ions, characterized in that: It is prepared by the reaction of aldehyde monomer trialdehyde phloroglucinol and amine monomer; The amine monomer is 2,5-diaminoterephthalic acid or 4,4'-diamino-[1,1'-biphenyl]-3,3'-dicarboxylic acid.
2. The acid-resistant COFs material for fast and efficient adsorption of thorium ions according to claim 1, characterized in that: The molar ratio of the aldehyde monomer to the amine monomer is 1:1-2.
5.
3. The method for preparing an acid-resistant COFs material for fast and efficient adsorption of thorium ions as claimed in claim 1, characterized in that: The specific steps include: adding aldehyde monomers and amine monomers into an organic solvent, ultrasonically mixing them evenly, then adding a catalyst, freezing with liquid nitrogen, evacuating, flame sealing, heating for crystallization, Soxhlet extraction, washing and drying to obtain the target COFs material.
4. The method for preparing an acid-resistant COFs material for fast and efficient adsorption of thorium ions as claimed in claim 1, characterized in that: The organic solvent is 1,4-dioxane and mesitylene in a volume ratio of 1:1-9 or n-butanol and o-dichlorobenzene in a volume ratio of 1:1-4.
5.
5. The method for preparing an acid-resistant COFs material for fast and efficient adsorption of thorium ions as claimed in claim 1, characterized in that: The solid-to-liquid ratio of the aldehyde monomer and the amine monomer to the organic solvent is 4.8-33.33 mg / mL.
6. The method for preparing an acid-resistant COFs material capable of rapidly and efficiently adsorbing thorium ions as claimed in claim 1, characterized in that: The catalyst is an acetic acid aqueous solution with a concentration of 6-12 mol / L; the volume ratio of the catalyst to the organic solvent is 1:5-9.
3.
7. The method for preparing an acid-resistant COFs material capable of rapidly and efficiently adsorbing thorium ions as claimed in claim 1, characterized in that: The ultrasonic time is 8-12 minutes.
8. The method for preparing an acid-resistant COFs material capable of rapidly and efficiently adsorbing thorium ions as claimed in claim 1, characterized in that: The temperature of the heating crystallization is 100-160° C., and the time is 3-9 days.
9. Use of the COFs material obtained by the preparation method according to any one of claims 3 to 8 in the rapid and efficient adsorption of thorium ions.
10. The use according to claim 9, characterized in that The pH of the thorium ion solution is 1-3.
Citation Information
Patent Citations
Preparation and application of covalent organic framework porous nano composite material
CN111871376A
Lithiation covalent organic framework composite polymer electrolyte as well as preparation and application thereof
CN112786960A
COFs (Covalent Organic Frameworks) solid electrolyte containing lithium carboxylate group as well as preparation method and application of COFs solid electrolyte
CN114421007A
Carboxyl-functionalized covalent organic framework / amino-functionalized biochar composite material as well as preparation method and application thereof
CN115920844A
Preparation method and adsorption application of novel magnetic carboxyl functionalized defect COF
CN116410480A
Cited By
Organic covalent material and preparation method thereof, composite adsorption film and preparation method and application thereof
CN119751784A
Organic covalent materials and their preparation methods, composite adsorption membranes and their preparation methods and applications
CN119751784B
Responsive porous material, preparation method and application thereof, intelligent membrane and preparation method and application thereof
CN119912656A
